The Interaction Between N6-Methyladenosine Modification and Non-Coding RNAs in Gastrointestinal Tract Cancers - Yao, Lin; Man, Chang-Feng; He, Rong; He, Lian; Huang, Jia-Bin; Xiang, Shou-Yan; Dai, Zhe; Wang, Xiao-Yan; Fan, Yu (Frontiers in Oncology, 2022)
N6-methyladenosine (m6A) is the most common epigenetic modification of eukaryotic RNA, which can participate in the growth and development of the body and a variety of physiological and disease processes by affecting the splicing, processing, localization, transport, translation and degradation of RNA. Increasing evidence shows that non-coding RNAs, particularly microRNA, long non-coding RNA, and circular RNA, can also regulate the RNA m6A modification process by affecting the expression of m6A-related enzymes. The interaction between m6A modification and non-coding RNAs provides a new perspective for the exploration of the potential mechanism of tumor genesis and development. In this review, we summarize the potential mechanisms and effects of m6A and non-coding RNAs in gastrointestinal tract cancers.